2014
DOI: 10.30638/eemj.2014.319
|View full text |Cite
|
Sign up to set email alerts
|

COST-EFFECTIVE MASS PROPAGATION OF VIRGINIA FANPETALS (Sida hermaphrodita (L.) Rusby) FROM SEEDS

Abstract: The primary objective of this research was to develop safe, programmable and cost-effective technologies of plantlet production from the seeds of undomesticated American populations of Virgina fanpetals (Sida hermphrodita RUSBY). During our seed priming treatment experiments, approximately 40% of the Virginia fanpetals seeds that were high-quality, infection-free, normally imbibing and germinating seeds. Our spring propagation tray experiments indicated that the spring large-scale tray plantlet production of V… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 9 publications
0
12
0
Order By: Relevance
“…Because of this, researchers have attempted to find ways of improving the germination rate. During a four year experiment, Kurucz et al [11] found no relationship between germination and storage period of the seeds. Franzaring et al [28] kept seeds that had been sown in seeding trays under controlled conditions for four weeks, with alternating temperatures of 3 • C and 11 • C to overcome dormancy.…”
Section: Establishment By Sowingmentioning
confidence: 96%
See 3 more Smart Citations
“…Because of this, researchers have attempted to find ways of improving the germination rate. During a four year experiment, Kurucz et al [11] found no relationship between germination and storage period of the seeds. Franzaring et al [28] kept seeds that had been sown in seeding trays under controlled conditions for four weeks, with alternating temperatures of 3 • C and 11 • C to overcome dormancy.…”
Section: Establishment By Sowingmentioning
confidence: 96%
“…It found its way to Poland as a fodder and fibre crop in the 1950s, where it was still used for these purposes in the 1980s [7]. Kurucz et al [11] described the first accidental introduction of the species into Hungary during the 1970s, after which S. hermaphrodita became more widespread through trade with Poland, to the point that in 2010 it was included in a list of species for which bioenergy funding could be obtained. In Poland, studies indicated that around 96 ha of S. hermaphrodita were cultivated in 2008 [12] and an additional 750 ha was planted up to 2011 [13].…”
Section: Origin and Botanymentioning
confidence: 99%
See 2 more Smart Citations
“…The most important requirements of phytoremediator plants are high tolerance against pollutants, fast growing with high yield, possible economical impact and they can remove, reduce, degrade or immobilize environmental pollutants in high extent (Pilon-Smits, 2005). Besides energy purposes biomass plants (Antal et al, 2014;Kurucz et al, 2014;Kurucz and Fári, 2013;Kurucz et al, 2012) have been moving to the forefront of interest using in phytoremediation. Generally these plants are not able to accumulate as much pollutants, than real hyperaccumulator species but considering their higher yield ultimately they can present great potential.…”
Section: Introductionmentioning
confidence: 99%